Study on the Optimization of Cu-Zn-Sn-O to Prepare Cu2ZnSnS4 Thin Film via a Nano Ink Coating Method - Li, Qian; Hu, Jinpeng; Cui, Yaru; Wang, Juan; Du, Jinjing; Wang, Miao; Hao, Yu; Shen, Tong; Duan, Lizhen; Wang, Simin; Sun, Ke (Frontiers in Chemistry, 2021)
To reduce the formation of impurity phase, buffer volume expands and smooth the surface of Cu2ZnSnS4(CZTS) thin film, Cu-Zn-Sn-O(CZTO) precursor was synthesized through the process of coprecipitation-calcination-ball milling-spin coating. The influence of pH, temperature, PVP on the constituent of hydroxides were investigated in the process of coprecipitation. Cu-Zn-Sn-O with appropriate compositions could be obtained by regulating temperature and preservation time of calcination stage. After ball milling to form a nano ink, and then spin coating, SEM images proved the generation of CZTO precursors which effectively promoted the formation of Cu2ZnSnS4 thin films. Finally, the phase, microstructure, chemical composition and optical properties of the Cu2ZnSnS4 thin films prepared by sulfurized annealing CZTO precursors were characterized by EDX, XRD, Raman, FESEM, Hall effect and UV methods. The prepared CZTS thin film demonstrated a band gap of 1.30 eV, which was suitable for improving the performance of CZTS thin film solar cells.